MEDIA BERBASIS ADOBE FLASH UNTUK PEMBELAJARAN KETERAMPILAN MENYIMAK DI PROGRAM STUDI PGSD - Biya Ebi Praheto; Andayani Andayani; Muhammad Rohmadi; Nugraheni Eko Wardani (Universitas Sarjanawiyata Tamansiswa, 2019)
Learning media always develops the following technological developments. Likewise, the media in learning is listening to Indonesian. The development of learning media is important. Adobe Flash-based media developed to facilitate lecturers and students in learning Indonesian listening skills in the Elementary School Teacher Education Study Program. Media that are designed to be interesting may not only train cognitive knowledge but also practice practical listening skills. Adobe Flash-based media for listening are designed by displaying several menus, namely the home menu, RPS (Semester Learning Plan), materials, practices, games, music, profiles, and references, as well as close menus appearing in accordance with the cross (x) to be used using the application. The hope media developed was able to assist lecturers in delivering learning material, as well as helping students learn well in the classroom and outside the classroom.